Retail trader pricing behavior in the traditional rice market: A micro view for curbing inflation - Feryanto; Harianto Harianto; Herawati (Cogent Economics & Finance, 2023)
The price of rice at the retail level affects consumer welfare and influences inflation. The research objective was to study rice retail trader pricing behavior in traditional markets. This study employed an econometric model consisting of six equations of price spread between the retail market level and wholesale level of different rice qualities and grades. To overcome endogeneity problems due to the use of several equations that could cause potential bias, the simultaneous method with the 3SLS approach was deemed appropriate to use to obtain consistent and efficient coefficient estimates. The results show that, by examining the behavior of price spreads in the model, it can be deduced that rice retailers in the traditional market applied a price stabilization strategy. A lower price spread responded to an increase in price at the wholesale level. Rice retailers in traditional markets also implemented a price-averaging strategy. The results of this study have important policy implications for reducing food price volatility and its impact on inflation. That is, a price policy aimed at price stabilization at the retail level, as in this study, will be more effective if the price stabilization is focused on the wholesale level. However, if the pricing policy continues to be applied at the retail level, it must consider the relationships between different rice qualities and prices. This study also highlights the need for more intensive research on pricing behavior at the wholesale level.
Keywords: D40; E31; E60; 330; COVID-19; inflation; price stabilization; rice; traditional market